Monitoring of Tissue Oxygenation: an Everyday Clinical Challenge - Molnar, Zsolt; Nemeth, Marton (Frontiers in Medicine, 2018)
Purpose of review: Overview of pathophysiology and clinical application of central venous oxygen saturation monitoring in critically ill patients and during the perioperative period. Recent findings: There are several clinical studies and animal experiments evaluating the effects of goal directed hemodynamic stabilization of critically ill patients. Recent systematic reviews and meta-analyses found that advanced hemodynamic endpoints targeted management has a positive effect on outcome in high risk surgical patients. As all interventions aim to improve tissue oxygenation it is of utmost importance to monitor the balance between oxygen delivery and consumption. For this purpose central venous blood gas analysis provides an easily available tool in the everyday clinical practice. The adequate interpretation of central venous oxygen saturation renders the need of careful evaluation of several physiological and pathophysiological circumstances. When appropriately evaluated, central venous oxygen saturation can be a valuable component of a multimodal individualized approach, in which components of oxygen delivery are put in the context of the patients’ individual oxygen consumption. In addition to guide therapy, central venous oxygen saturation may also serve as an early warning sign of inadequate oxygen delivery, which would otherwise remain hidden from the attending physician. Summary: With the incorporation of central venous oxygen saturation in the everyday clinical routine, treatment could be better tailored for the patients’ actual needs hence it may also improve outcome.